Făgăraș as Jerusalem? Interethnic and interreligious ethos in Transylvania - Iulian, Toroczkai C. (HTS teologiese studies, 2017)
The study presents Transylvania as a space of ethnic-religious tolerance, having as a case studythe image of the town Făgăraș, as depicted in Eginald Schlattner’s novels. This space appearsas one of a heavenly nuance, based on a long tradition of coexistence of the members ofdifferent ethnic groups and religions. However, the inter-war and post-war period means theemergence of new challenges posed by the confrontation with the harmful effects of the twoideologies: Nazism and Communism. In this way, the dramas of the socio-historical contextinterweave with elements forming young Eginald. They will remain a constant in the writer’slife, offering Făgăraș the role of a forming educational array, with a paradigmatic value.